Footprints of Surprise: A 4-Year Odyssey of an Intruder in a Teenage Foot- A Case Report - Shakya, Amir Ratna; Singh, Alok; Kayastha, Nirab; Sinha, Ritesh; Magar, Mohit Thapa (Nepal Orthopaedic Association Journal, 2024)
Glass foreign body injuries, especially in the foot, are common occurrences in our part of the world owing to barefoot walking practice. Despite exploration, there are chances of retention of foreign bodies in the wound which can later result in complications such as chronic pain, granuloma formation, infection, and secondary migration features. Here we present a case of a teenage girl with a retained glass foreign body in her foot for a duration of 4 years which had been missed in the first visit to a health facility.